2001
DOI: 10.1590/s1415-52732001000200003
|View full text |Cite
|
Sign up to set email alerts
|

Desnutrição e resultados de reabilitação em Fortaleza

Abstract: RESUMO RESUMO RESUMO RESUMO RESUMO Este estudo teve por objetivo caracterizar a prevalência da desnutrição e o percentual de reabilitação nutricional entre crianças assistidas pelo Programa de Assistência ao Desnutrido e à Gestante de Risco

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
7

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
1
7
0
7
Order By: Relevance
“…12 In a literature review including 38 anthropometric surveys conducted with children of up to five years old, the authors also found that this index was highly compromised. 13 This finding was corroborated by other studies carried out in other cities 14 and also in Porto Alegre. [15][16][17] A slight male predominance was observed among the evaluated children.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…12 In a literature review including 38 anthropometric surveys conducted with children of up to five years old, the authors also found that this index was highly compromised. 13 This finding was corroborated by other studies carried out in other cities 14 and also in Porto Alegre. [15][16][17] A slight male predominance was observed among the evaluated children.…”
Section: Discussionsupporting
confidence: 80%
“…Higher rates of noncompliance, between 19 and 30%, were found by other authors 11,19,22,23 in Brazilian programs for nutritional supplementation. Only Soares & Parente 14 found a lower rate of noncompliance (9.6%).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations